Bio mathematical venture for the metallic nanoparticles due to ciliary motion. Issue 134 (October 2016) - Akbar, Noreen Sher; Butt, Adil Wahid
Highlights: The effect of cilia motion is deliberated by the fluid model of metallic nanoparticles. Two types of fluid nanoparticles (i.e. Cu Water nanofluid and pure Water nanofluid) are discussed. The problem is formulated in a symmetric channel with ciliated walls. Exact solutions of the governing problem are obtained for pressure gradient, temperature and velocities of the fluid. Streamlines for the velocity profile are plotted to discuss the trapping phenomenon. Abstract: Background and Objectives: The present investigation is associated with the contemporary study of viscous flow in a vertical tube with ciliary motion. Methods/Results/Conclusions: The main flow problem has been modeled using cylindrical coordinates; flow equations are simplified to ordinary differential equations using longwave length and low Reynold's number approximation; and exact solutions have been obtained for velocity, pressure gradient and temperature. Results acquired are discussed graphically for better understanding. Streamlines for the velocity profile are plotted to discuss the trapping phenomenon. It is seen that with an increment in the Grashof number, the velocity of the governing fluids starts to decrease significantly.